Banks and innovation: Microeconometric evidence on Italian firms☆ - BENFRATELLO, L; SCHIANTARELLI, F; SEMBENELLI, A (Journal of Financial Economics, 2008)
In this paper we investigate the effect of local banking development on firms’ innovative activities, using a rich data set on innovation for a large number of Italian firms over the 1990s. There is evidence that banking development affects the probability of process innovation, particularly for firms in high-tech sectors, in sectors more dependent upon external finance, and for firms that are small. The evidence for product innovation is much weaker and not robust. There is also some evidence that banking development reduces the cash flow sensitivity of fixed investment spending, particularly for small firms, and that it increases the probability they will engage in R&D.